Percutaneous removal of a knotted pulmonary artery catheter using a tracheostomy dilator - Akkerhuis, Marja Jagers op (BioMed Central, 1999)
This case report describes removal of a knotted, subclavian, pulmonary artery catheter using a tracheostomy dilator. With this simple method an invasive procedure might be averted.